(untitled) (Journal of Informatics and Mathematical Sciences, 2018)
A steady two dimensional hydromagnetic flow through a uniform channel covered by porous media having finite thickness is considered. A uniform magnetic field is applied in the perpendicular direction of the motion of the fluid. Since, it is assumed that the thickness of the porous media is smaller than the width of the flow channel, analytical solutions are obtained by using Beavers-Joseph-Rudraiah slip condition. Expressions for primary and secondary velocities and the shear stress are obtained. These expressions have been computed for different values of the Hartmann number, Hall parameter, Darcy velocity, the porous parameter and width of the porous medium. The effects of these parameters on both primary and secondary velocities and shear stress have been investigated.